Di-Alkyl Adipates as New Phase Change Material for Low Temperature Energy Storage - Sequeira, Maria C. M.; Nogueira, Bernardo A.; Caetano, Fernando J. P.; Diogo, Herminio P.; Fareleira, Joao M. N. A.; FAUSTO, RUI (Springer/Plenum Publishers, 2023)
This work is a contribution to the thermal characterization of a selected binary system of two di-n-alkyl adipates that can be used as phase change material for thermal energy storage at low temperatures. The construction of the solid-liquid phase diagram using differential scanning calorimetry (DSC), complemented with Raman Spectroscopy studies for the system composed by diethyl and dibutyl adipates is presented. The solidus and liquidus equilibrium temperatures were determined by DSC for the pure components and 30 binary mixtures at selected molar compositions were used to construct the corresponding solid-liquid phase diagram. The binary system of diethyl and dibutyl adipates presents eutectic behaviour at low temperatures. The eutectic temperature was found at 240.46 K, and the eutectic composition was determined to occur at the molar fraction xdibutyl = 0.46. Additionally, the system shows a polymorphic transition, characteristic of dibutyl adipate, occurring at ca. 238 K, confirmed by optical microscopy. To the best of our knowledge, no reference to the phase diagram of the present system could be found in the literature. Raman spectroscopy was essential to complement the construction of the phase equilibrium diagram, enabling the identification of the solid and liquid phases of the system. Finally, the liquidus curve of the phase diagram was also successfully predicted using a suitable fitting equation, being the root mean square deviation of the data from the correlation equal to 0.54 K. In addition, this fitting operation enabled a correct prediction of the eutectic composition of the system.
Keywords: Adipates; Binary Phase Diagram; Energy Storage; Eutectic; PCM; Phase Change Material; Polymorphism